Four cases of extracranial abscess caused by sinusitis exacerbated by a foreign body - Kazuhiro Takahashi; Muneo Nakaya (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2018)
Background: Foreign bodies in the paranasal sinus is a relatively rare. Furthermore, most of foreign bodies in the paranasal sinuses occur in the maxillary sinus, and reports of foreign bodies in frontal sinus are few. Extracranial abscesses caused by sinusitis with foreign bodies is a rare, but it sometimes cause serious complications. We report four cases of extracranial abscess caused by sinusitis exacerbated by a foreign body. Case report: In all four cases, temporal subcutaneous abscess developed 10 or more years after receiving craniotomy. A CT scan revealed the frontal sinus had traffic to the plate and a subcutaneous abscess was observed around the plate. In three cases, a drainage route was created by endoscopic sinus surgery, and in two cases, Draf type Ⅲ was performed. However, the infection due to foreign matter did not improve, and it cured by removing residual foreign matter. In one case, symptoms were improved by creating a drainage route, and removal of foreign matter was unnecessary. Conclusion: Infection of the frontal sinuses by a foreign body requires the creation of a drainage route, although it is sometimes necessary to remove the foreign body if the infection continues even after drainage.